Chilaiditi syndrome: A structural displacement in a heart failure patient. (August 2021) - Song, David; Seen, Tasur; Almas, Talal; Ireifej, Branden; Kupferman, Judah; Khedro, Tarek; Alshamlan, Abdulaziz; Abdulhadi, Abdulaziz; Sattar, Yasar; Alraies, M. Chadi
Abstract: Background: Chilaiditi's sign is often found incidentally on chest or abdominal radiograph and can be accompanied by clinical symptoms such as abdominal pain, gastrointestinal complications, and less commonly associated with dyspnea. Case presentation: In this interesting case, we discover lingering dyspnea in our 79 year old male with a past medical history of asthma and heart failure with preserved ejection fraction admitted for acute heart failure exacerbation with reduced ejection fraction along with a new incidental finding of Chilaiditi's sign on chest radiograph. Patient received optimal diuretics and guideline-directed medical treatment for heart failure exacerbation, but mild dyspnea with pleuritic chest pain persisted. Dyspnea with pleurisy was likely attributed to a structural anatomical defect (Chilaiditi's sign) that can be picked up on imaging. Conclusion: Chilaiditi syndrome can be an incidental cause of ongoing persistent dyspnea, and if symptoms are severe, intervention can be warranted for symptomatic resolution. Learning objective: Chilaiditi syndrome should be considered as a possible diagnosis among patients with a history of heart failure and incidental Chilaiditi's sign on chest radiographic imaging who suffer from persistent dyspnea and pleurisy despite optimal diuretics and guideline-directed medical treatment. Highlights: Chilaiditi's sign in an incidental finding on chest or abdominal radiograph associated with gastrointestinal symptoms and less commonly associated with dyspnea. Chilaiditi's sign with underlying heart failure is not well understood. Chilaiditi syndrome should be considered as a possible diagnosis among patients with a history of heart failure and incidental Chilaiditi's sign on chest radiographic imaging who suffer from persistent dyspnea and pleurisy despite optimal diuretics and guideline-directed medical treatment.